GOOD FAITH IN TRIPS COMPULSORY LICENSING OF PHARMACEUTICAL PATENTS: LESSONS FROM PREVIOUS PANDEMIC CASES - Muhammad Ardiansyah Arifin (Faculty of Law Universitas Lampung, 2021)
The COVID-19 pandemic impacts the world of patents as countries prepare their legal framework to ease the process of compulsory licensing. Some like India and South Africa even went further by proposing a suspension for patents needed to combat COVID-19 which is still under discussion. It is a real possibility that a patented drug that is effective against COVID-19 would potentially see compulsory licensing in many countries its patent holder is doing business. This article discusses why compulsory licensing is an essential issue by examining its legitimacy, previous cases of compulsory licensing, and the conduct of states in cases of compulsory licensing issuance, particularly in examples of Thailand, Brazil, and India. The article will examine ways of remedy against compulsory licensing, including a theoretical possibility for constitutional review of treaties. The remedies discussed shall include international and domestic remedies, both litigation and alternative measures. The research shall use qualitative research methods with the use of primary and secondary legal sources. The result of this article found that a combination of soft law power of the Doha Declaration and the invocation of subsequent compulsory licensing cases be the support pillars of compulsory licensing practice. However, the practice of compulsory licensing both by the patent holder and the state actors is still not performed entirely in good faith according to the Vienna Convention of the Law of Treaties (VCLT) 1969 and the TRIPS Agreement. Hence, such patent holders need to be familiar with both international and domestic remedies, especially the possibility for constitutional review of treaties remedies.